Nachträglichkeit: A Freudian perspective on delayed traumatic reactions. (October 2014) - Bistoen, Gregory; Vanheule, Stijn; Craps, Stef
The Freudian concept of Nachträglichkeit is central to the psychoanalytical understanding of trauma. However, it has not received much attention within the contemporary field of trauma studies. This paper attempts to reconstruct the logic inherent to this concept by examining Freud's remarks on the case of Emma. Furthermore, it is argued that Nachträglichkeit offers an interesting perspective on both (a) the well-established yet controversial finding that traumatic reactions sometimes follow in the wake of non-Criterion A events (so-called minor stressors or life events) and (b) the often-neglected phenomenon of delayed-onset PTSD. These two phenomena will appear to be related in some instances. Nachträglichkeit clarifies one way in which traumatic encounters are mediated by subjective dimensions above and beyond the objective particularities of both the event and the person. It demonstrates that the subjective impact of an event is not given once and for all but is malleable by subsequent experiences.